Alkaline Phosphatase Expression From Mice Mesenchymal Stem Cells Induced By Flamboyant Flower (Delonix regia) Extract - Eriani, Kartini; Anggraini, Deby; Bintoro, Yudha; Ichsan, Ichsan; Azhar, Al; Mariya, Silmi (Department of Biology, Faculty of Mathematics and Sciences, Semarang State University . Ro, 2020)
Flamboyant flower (Delonix regia) extract can increase proliferation and differentiation rates of mesenchymal stem cells (MSCs) into specific cells such as bone, nerve, and fibroblast cells. The extract possess metabolic compounds that may act as antibiotics, anti-inflammatory, antimicrobial, diuretic, anthelmentic, astringent, leucorrhoea, and potentially increase the body's metabolism normally. This study aimed to investigate expression level of alkaline phosphatase (ALP) by mice MSCs treated with flamboyant flower extract in vitro. Here, mice bone marrow cell cultures were treated with flamboyant flower extracts of 0.6 mg/ml (P1), 0.7 mg/ml (P2), 0.8 mg/ml (P3), and 0.9 mg/ml (P4). Untreated cell culture was used as negative control (P0). Expression of ALP gene was measured by RT-qPCR method. The results showed that mice mesenchymal stem cell could differentiate into bone, nerve, and fibroblast cells. The addition of flamboyant flower extract ranged from 0.6-0.9 mg/ml significantly (p<0.05) influenced the expression of ALP by differentiating MSCs. The highest expression was found at the stem cells treated with flamboyant flower extract of 0.8 mg/ml, 0.13 times compared with control. In conclusion, flamboyant flower extracts treatment might increase the expression of ALP in differentiating MSCs. Â This information can be used as a basis for finding an appropriate biomarkers for tracking the differentiation and profileration of tissue originated MSCs induced by extracts of medicinal plants.